2010
DOI: 10.1074/jbc.m110.151076
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interferon α (IFNα)-inducible Schlafen-5 in Regulation of Anchorage-independent Growth and Invasion of Malignant Melanoma Cells

Abstract: IFN␣ exerts potent inhibitory activities against malignant melanoma cells in vitro and in vivo, but the mechanisms by which it generates its antitumor effects remain unknown. We examined the effects of interferon ␣ (IFN␣) on the expression of human members of the Schlafen (SLFN) family of genes, a group of cell cycle regulators that mediate growth-inhibitory responses. Using quantitative RT-real time PCR, we found detectable basal expression of all the different human SLFN genes examined (SLFN5, SLFN11, SLFN12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 60 publications
4
113
1
Order By: Relevance
“…Another example is DOCK9 (dedicator of cytokinesis 9), which belongs to the Dock family of evolutionarily conserved exchange factors for the Rho GTPases Rac and Cdc42, regulating actin cytoskeleton, cell adhesion, and migration (48). SLFN5, a protein, was described to have a key role in controlling motility and invasiveness of renal cell carcinoma and melanoma cells (49,50). SLFN5 negatively controls expression of matrix metalloproteinases (MMP), and several other genes involved in the control of malignant cell motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is DOCK9 (dedicator of cytokinesis 9), which belongs to the Dock family of evolutionarily conserved exchange factors for the Rho GTPases Rac and Cdc42, regulating actin cytoskeleton, cell adhesion, and migration (48). SLFN5, a protein, was described to have a key role in controlling motility and invasiveness of renal cell carcinoma and melanoma cells (49,50). SLFN5 negatively controls expression of matrix metalloproteinases (MMP), and several other genes involved in the control of malignant cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…S2C). Cell lines were treated with E7438 at the calculated IC 50 value from proliferation assays, to compare the cycle effects at a similar inhibition level. We observed a general decrease in the percentage of cells in G 2 -M accompanied by an increase in sub-G 1 (apoptotic) cells, except for the U-266 cell line which showed only a minor increase in the G 0 -G 1 fraction.…”
Section: Ezh2 Inhibition Induces Time-dependent Antiproliferative Effmentioning
confidence: 99%
“…Assays using the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-tetra-zolium bromide method were performed after treating cells with IFN␣ for 5 to 7 days, as in our previous studies (9,18).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we demonstrated that among human SLFNs, SLFN5 is selectively up-regulated in response to IFN treatment in malignant melanoma cells (18). In the present study, we undertook a systematic analysis on the IFN-inducible expression and biological relevance of different mouse Slfn genes in mouse malignant melanoma and renal cell carcinoma (RCC) 2 cells.…”
Section: There Is Emerging Evidence That the Ifn-inducible Family Ofmentioning
confidence: 99%
See 1 more Smart Citation